‘Malenkey Robot’ in the Carpathian Basin, in Hungary – Data, Facts, Interpretations, Connections - Bognár Zalán (Acta Universitatis Sapientiae: European and Regional Studies, 2015)
Interpretation problems related to the notion of ‘malenkaya rabota,’ POW, internee, GULAG and GUPVI. Ways of classification of the victims of ‘malenkaya rabota' in the Carpathian Basin, various groups and types. Determination of the effective number of the groups, and of the total number of those deported as civilians from the 14.7 million inhabitants of the Hungary of the time, based on different data, and the difficulties of definitions. The interpretation and implementation of the central Soviet commands. The connections between the deportations. Similarities and differences between the deportations as internee and as POW. Manageability of the data, interpretation of Soviet and Hungarian archive data and the reasons why they are different. The real value of Soviet archival sources. The determination of the losses attributed to ‘malenkaya rabota’.